IMPORTANCE OF RISK MAP IN THE MANAGEMENT OF RISKS THAT MAY OCCUR IN COMMERCIAL BANKS - Muqumov Orifjon Abduroziqovich (American Journals, 2023)
The article provides information on the types of risks that may arise in commercial banks of the Republic of Uzbekistan, as well as the importance of using the Risk Map in preventing and managing these risks.
Keywords: risk, types of risk, register of risk events, risk map, risk codes, risk management strategy.